2017
DOI: 10.1063/1.5009003
|View full text |Cite
|
Sign up to set email alerts
|

High detectivity visible-blind SiF4 grown epitaxial graphene/SiC Schottky contact bipolar phototransistor

Abstract: We report the performance of a bipolar epitaxial graphene (EG)/p-SiC/n+-SiC UV phototransistor fabricated with a Schottky (EG)/SiC junction grown using a SiF4 precursor. The phototransistor showed responsivity as high as 25 A/W at 250 nm in the Schottky emitter (SE) mode. The Schottky collector (SC) mode showed a responsivity of 17 A/W at 270 nm with a visible rejection (270 nm:400 nm)>103. The fastest response was seen in the SC-mode, with 10 ms turn-on and 47 ms turn-off, with a noise equivalent power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In this paper, we create spatially and electronically separated QD/EG and QD/SiC junctions to isolate the remaining PbS-QD/SiC interface. This enabled separate examination using localized illumination for scanning photocurrent microscopy (SPCM). , The architecture presented in Figure enabled us to exploit the following phenomenological observations to achieve this: (i) ohmic contacts of graphene to ethanedithiol (EDT)-capped PbS QDs in air, consistent with p-type conduction reported previously, which was also verified in the current work; (ii) a robust and ideal Schottky diode of EG/SiC that is shown in this paper to be completely recoverable by selective chemical removal using hydrofluoric acid; (iii) a 10–15 monolayer (ML) EG film that achieves optical transparency for optoelectronic characterization, while having a thickness greater than 1–2 ML screening length, such that electrostatic screening of the EG/SiC rectifying junction from the ohmic EG/PbS-QD film junction is achieved, precluding any potential barristor action. , This confluence of favorable conditions eliminates uncertainties stemming from the reproducibility of contacts between samples and between successive PbS-QD film depositions.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this paper, we create spatially and electronically separated QD/EG and QD/SiC junctions to isolate the remaining PbS-QD/SiC interface. This enabled separate examination using localized illumination for scanning photocurrent microscopy (SPCM). , The architecture presented in Figure enabled us to exploit the following phenomenological observations to achieve this: (i) ohmic contacts of graphene to ethanedithiol (EDT)-capped PbS QDs in air, consistent with p-type conduction reported previously, which was also verified in the current work; (ii) a robust and ideal Schottky diode of EG/SiC that is shown in this paper to be completely recoverable by selective chemical removal using hydrofluoric acid; (iii) a 10–15 monolayer (ML) EG film that achieves optical transparency for optoelectronic characterization, while having a thickness greater than 1–2 ML screening length, such that electrostatic screening of the EG/SiC rectifying junction from the ohmic EG/PbS-QD film junction is achieved, precluding any potential barristor action. , This confluence of favorable conditions eliminates uncertainties stemming from the reproducibility of contacts between samples and between successive PbS-QD film depositions.…”
Section: Introductionsupporting
confidence: 78%
“…We have recently explored optoelectronic properties of Schottky diodes and bipolar phototransistors based on the tetrafluorosilane (SiF 4 , TFS) grown contacts of epitaxial graphene (EG) on a SiC substrate to form a graphene/WBG interface. These devices are sensitive to ultraviolet light based on the bandgap of 4H-SiC. Here, we demonstrate that these devices respond to NIR light as a direct consequence of the rectifying junction formed between the QD film and n-type 4H-SiC.…”
Section: Introductionmentioning
confidence: 94%
“…The detectivity of the PDs, which is indicative of their overall performance, is given as where A (cm 2 ) is the total exposure area of the PD, including the metalized areas (see Figure (a)), B (Hz) is the bandwidth, and NEP (W) is the noise equivalent power of the PD. To determine the NEP of our PD, we first estimated the total noise power which is equal to the sum of the shot noise power P s (Ampere 2 ) and the 1/ f flicker noise power P 1/ f (Ampere 2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the 1/ f flicker noise is dominant in the range of 1 to 100 Hz, while after 100 Hz, the noise spectrum becomes flat. For a bandwidth of B , the total flicker noise current was given as , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Further, we compared the device performance to those of other UV photodetectors, including graphene/4H-SiC-based photodetectors, [11,14,17,37,[50][51][52] as shown in Table 1. Our devices showed a higher R with a relatively lower working voltage.…”
Section: Resultsmentioning
confidence: 99%